757 ASSESSING THE READMISSION RATES OF THE OLDER PERSON'S ASSESSMENT AND LIAISON ACUTE FRAILTY TEAM AT GOOD HOPE HOSPITAL. (8th March 2022) - Brice, H G T; Sheikh, S; Quigley, T
Abstract: Introduction: The Older Person's Assessment and Liaison (OPAL) team at Good Hope Hospital (GHH), part of the University Hospitals Birmingham NHS Foundation Trust, provides multidisciplinary, patient-centred comprehensive assessment to patients presenting to the hospital front door. The team takes a 'home first' approach and where possible aims to discharge patients home with support by community teams. The service is part of the Birmingham wide Early Intervention programme. A front door OPAL service therefore enables early discharge for frail patients who would otherwise be likely to have a prolonged hospital admission. This has to be balanced against ensuring readmission rates do not exceed that of a comparable hospital inpatient population. Method: We measured the 7 and 28-day readmission rate of all patients who received OPAL input and were discharged from A&E, the Medical Admissions Unit or the Acute Medical unit from July 2020—January 2021. This was compared with an inpatient short stay frailty unit however data was not available beyond November 2020 due to changes in response to the Covid-19 pandemic. Results: 2096 patients were discharged by OPAL with a 7-day readmission rate of 9.2% (95% CI 4.6–13.7%) and a 28-day readmission rate of 20.2% (95% CI 14.0–26.4%). From July—October 2020 the short stay frailty unit at GHH had a 7-day readmission rate of 9.7% (95% CI 3.1–16.3%) and a 28-day readmission rate of 25.2% (95% CI 8.2–42.2%). In the same period OPAL had a 7-day readmission rate of 8.7% (95% CI 3.2–14.2%) and a 28-day readmission rate of 19.9% (95% CI 13.3–26.5%). Conclusion: The OPAL service enabled the early discharge of patients without compromising readmission rates. The readmission rates for patients discharged by the OPAL team were better than the inpatient frailty unit with over 20% fewer 28 day readmissions.